Being and Film A Fictive Ontology of Film in Tarkovsky's Solaris. - Reeh-Peters, Christine (Cambridge Scholars Publisher, 2021)
This book develops the so-called ""solaristic ontology"" of film by building a philosophical system based on an inquiry into the nature of film, being and reality. This ""solaristic system"" appropriates the aesthetic ideas and principles of thought present in the 1972 sci-fi movie Solaris by Andrei Tarkovsky. This movie is the main center of analysis here since it is highly symptomatic of the medium's philosophical self-reflexivity and its intriguing correlation with reality and being. The ""solaristic science"" is a fictional science introduced in the movie's diegesis and dedicated to the in.